Urinary tract infections in neonates with unexplained pathological indirect hyperbilirubinemia: Prevalence and significance - Elif Bahat Ozdogan; Mehmet Mutlu; Secil Arslansoyu Camlar; Gülcin Bayramoglu; Sebnem Kader; Yakup Aslan (Pediatrics and Neonatology)
Background: It is controversial to test for urinary tract infection (UTI) in patients with unexplained indirect hyperbilirubinemia in the first 2 weeks of life. We aimed to study the prevalence and significance of UTIs in such neonates who were requiring phototherapy. Methods: Subjects were 2- to 14-day-old neonates with indirect bilirubin levels above phototherapy limit with no other abnormality in their bilirubinaemia-related etiologic workup. UTI was diagnosed by 2 consecutive positive cultures obtained by catheterisation, documenting growth of >10,000 colonies of the same microorganism with consistent antibiograms. The UTI (+) patients were evaluated by renal ultrasonography (US), and some were followed up for possible recurrent UTI. Results: 262 neonates were included in the study. UTI prevalence was 12.2%, and bacteraemia was 6.2% among UTI (+) patients. The two most common pathogens (81.2%) were Escherichia coli and Klebsiella. pneumonia. All UTI (+) patients had undergone US, revealing 12.5% pelvicaliectasis, other 12.5% increased renal parenchymal echogenicity, 3.1% concurrent pelvicaliectasis and increased renal parenchymal echogenicity. 53.1% of UTI (+) patients had undergone follow-up, after which 23.5% recurrent UTI were found at the end of a mean of 52 months. Conclusion: We suggest that the neonates with unexplained pathological jaundice should be tested for possible UTI. Consequently, all newborns with UTI shall be evaluated by the urinary US and followed up for recurrent UTI.